2012
DOI: 10.1182/blood-2012-05-429514
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric-type nodal follicular lymphoma: an indolent clonal proliferation in children and adults with high proliferation index and no BCL2 rearrangement

Abstract: Pediatric follicular lymphoma (PFL) is a variant of follicular lymphoma (FL) presenting as localized lymphadenopathy in children. Unlike conventional adult FL, PFL typically does not recur or progress. Clear diagnostic criteria for PFL are lacking, and it is uncertain whether this indolent lymphoma is defined by age or may occur in adults. We analyzed 27 FL in patients < 40 years of age and found that all 21 cases that lacked a BCL2 gene abnormality (BCL2-N; P < .0001) and had > 30% Ki67 fraction (high prolife… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
115
4
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 131 publications
(132 citation statements)
references
References 37 publications
3
115
4
6
Order By: Relevance
“…In these cases, CD10 was negative in 37%; there was lack of BCL2 rearrangement in 89% and presence of BCL6 rearrangement in 35%. Unlike Louissaint et al, 9 who found all BCL2 rearrangement-negative/highprofoliferative index (BCL2-N/HPI) cases to be stage I among 58 adult follicular lymphoma studied (Z18 years of age), in our series, just onethird were stage I follicular lymphoma. Liu et al 8 found expression of MUM1/IRF4 in all pediatric follicular lymphoma cases involving the Waldeyer ring.…”
Section: Discussioncontrasting
confidence: 93%
See 2 more Smart Citations
“…In these cases, CD10 was negative in 37%; there was lack of BCL2 rearrangement in 89% and presence of BCL6 rearrangement in 35%. Unlike Louissaint et al, 9 who found all BCL2 rearrangement-negative/highprofoliferative index (BCL2-N/HPI) cases to be stage I among 58 adult follicular lymphoma studied (Z18 years of age), in our series, just onethird were stage I follicular lymphoma. Liu et al 8 found expression of MUM1/IRF4 in all pediatric follicular lymphoma cases involving the Waldeyer ring.…”
Section: Discussioncontrasting
confidence: 93%
“…Recently, follicular lymphoma occurring in children was characterized in detail. 8,9 We undertook the current study on an extensive cohort of young adults between the ages of 19 and 40 years, because of the dearth of knowledge regarding the clinicopathologic features and the outcome in patients diagnosed with follicular lymphoma in that age group. Most follicular lymphoma cases in patients o40 years are manifested in the older age subgroups within this population (35-39 years) and are more common in female population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, BCL6 and MYC aberrations typically associated with aggressive B-cell lymphomas are absent. 57,58,61,62 Overlap with florid follicular hyperplasia remains a practical and theoretical problem, as most PTFL lack specific genetic aberrations, and whether some of these cases may represent limited clonal expansions in florid follicular hyperplasia is still a subject of debate. 63 Nodal PTFL is an indolent disease with a very good prognosis.…”
Section: Pediatric Variant Of Follicular Lymphoma/pediatric-type Follmentioning
confidence: 99%
“…57,58 Known as the pediatric variant or pediatric type of FL (PTFL), it differs from the adult counterpart morphologically, immunophenotypically, and genetically. 59,60 It presents predominantly in young males, most often as isolated cervical lymphadenopathy.…”
Section: Pediatric Variant Of Follicular Lymphoma/pediatric-type Follmentioning
confidence: 99%